Voluntary Renunciation from Criminal Attempts, the Intersection of Public Order and Rehabilitation: A Comparative Overview - Farrokhi, Mansour; Sadeghi, Mohammad (Revue jurisprudence, 2019)
Criminal law comprises retributive sanctions as well as preventive measures in order to preserve public order and security. Even the rehabilitation of offenders is intended to provide public tranquillity. However, to achieve this goal requires the penalization of attempted crimes as a pre-emptive action so that official authorities can intervene to combat potential dangerous activities. Nevertheless, voluntary renunciation from such activities may eliminate the possible danger of the prohibited act. Additionally, it is often indicative of remorsefulness of the perpetrator. It can justify the exemption of the offender from criminal liability. Thus, it is ethically unreasonable to punish a person who voluntarily desists from a criminal attempt. However, there is sharp disagreement over the legal nature of voluntary renunciation. It has been shown in the present paper that there is a wide-ranging discussion on the basis and status of voluntary renunciation in criminal law. The main aim of this article is to provide a comparative overview of the matter, but it has to be preceded by explaining the concept of voluntary renunciation as well as the distinction between renunciation and withdrawal.